Tensile properties of styrene-ethylene-butadiene-styrene toughened and glass fiber reinforced polyethylene - Wong, Ngiap Han. (2010)
Polyethylene composites reinforced with glass fibers and elastomer-toughened with styrene-ethylene-butadiene-styrene were prepared using extrusion and then compression molded to form tensile bars conforming to the ASTM D-638 testing standards. Varying amounts of glass fibers and SEBS elastomers were incorporated into the sample in order to determine its effect on the tensile properties of the composites.